The effect of laying hen strain on perching biomechanics and keel deviations - Emily DePaoli; Doug Korver; Clover Bench (Journal of Applied Poultry Research)
SUMMARY: Keel bone damage (KBD), including deviations and fractures, is a welfare concern in laying hens leading to pain and decreased egg production. Shifting towards alternative housing systems has highlighted a need to evaluate how laying hen strain and perch shape contributes to perching biomechanics and KBD. Our study aimed to determine the effect of strain on perching biomechanics, keel deviations, body weight, and bone composition. Four commercial strains (Lohmann White, Shaver White, Lohmann Brown, ISA Brown) and two random-bred strains (Shaver Rhode Island Red and Antique White Leghorn) were studied (n = 20/treatment). Perching kinematics were evaluated on round and mushroom-shaped perches at 18, 29, and 70 weeks of age using continuous kinematic recordings. Instability indicators while perching included movement speed and motion in the x- (side-side), y- (forward-backward), and z-axes (up-down). Dual x-ray absorptiometry was used to assess bone parameters (femur and keel bone mineral content and density). Keel deviation severity was assessed via digital imaging post-mortem. Rhode Island Red hens had greater femur bone mineral density and content compared with all other strains evaluated. Higher-producing commercial strains had more incidences of severe keel deviations. Round perches led to faster forward-backward and up-down movements compared to mushroom perches. Commercial strains moved up-down more and forward-backward less than random-bred strains. Up-down movements were correlated with higher incidences of severe keel deviations. Overall, both strain and perch shape effected perching biomechanics. Specifically, round perches contributed to instability while perching. Commercial strains with more severe keel deviations moved up-down more than random-bred strains.